Intervensi Peningkatan Kemampuan Komunikasi pada Anak dengan Autism Spectrum Disorder (ASD): Sistematik Review - Salsabella, Natasya Mutiara; Iswinarti, Iswinarti (Universitas Muhammadiyah Metro, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects social interaction, communication, and behavior. Children with ASD often struggle to understand and interpret communication, impacting their social interactions. Various interventions have been developed to improve communication skills in children with ASD, such as PECS, music therapy, DIR Floortime, Aided Language Stimulation, flashcard play, Rolling Picture media, and Discrete Trial Teaching with a JASP+EMT+SGD approach. This study aims to identify and analyze these interventions through a systematic review approach. The findings indicate that appropriate interventions can help children with ASD develop their communication skills. These findings are expected to serve as a reference for parents, educators, and practitioners in selecting suitable intervention methods to support the communication development of children with ASD.